2013
DOI: 10.3109/10641955.2013.796970
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide methylation profiling demonstrates hypermethylation in maternal leukocyte DNA in preeclamptic compared to normotensive pregnancies

Abstract: ObjectiveTo compare genome-wide methylation profiles in maternal leukocyte DNA between normotensive and preeclamptic pregnant women at delivery.MethodsAge, body mass index matched case-control comparison of methylation at 27,578 cytosine—guanine sites in 14,495 genes in maternal leukocyte DNA in women with preeclampsia (PE; n = 14) and normotensive controls (n = 14).ResultsPE was associated with widespread differential methylation favoring hypermethylation. Pathway analysis identified the best matched process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 28 publications
1
34
0
1
Order By: Relevance
“…GO terms enriched for loci differing between controls and non-medicated mothers with depression or anxiety consisted mostly of terms related to transcription and translation of DNA, although methylation differences were small; the authors found no loci associated with SSRI use. White et al (2013) assayed blood via 27K to compare 14 pregnant women having preeclampsia to 14 normotensive controls [15]. None of the 19 top hits were suggestive of immune or inflammatory processes, although none were significant after adjusting for multiple comparisons.…”
Section: Pregnancy and Birthmentioning
confidence: 99%
See 1 more Smart Citation
“…GO terms enriched for loci differing between controls and non-medicated mothers with depression or anxiety consisted mostly of terms related to transcription and translation of DNA, although methylation differences were small; the authors found no loci associated with SSRI use. White et al (2013) assayed blood via 27K to compare 14 pregnant women having preeclampsia to 14 normotensive controls [15]. None of the 19 top hits were suggestive of immune or inflammatory processes, although none were significant after adjusting for multiple comparisons.…”
Section: Pregnancy and Birthmentioning
confidence: 99%
“…Because access to blood specimens is typically much more convenient to obtain from human subjects, the bulk of published studies have used whole blood (sometimes referred to as peripheral blood). A wide variety of phenotypes and health conditions have been studied: aging [4][5][6][7][8], cancer [9][10][11][12], obesity [5,13], cardiovascular disease [14], prenatal exposures/perinatal outcomes [15,16], environmental exposures [17][18][19][20][21][22][23][24] (tobacco in particular [25,26]), inflammatory diseases [27, 28•], psychiatric conditions [21,[29][30][31][32], and fertility [33]. While many of these studies have used candidate gene approaches with bisulfite-pyrosequencing, an increasing number have conducted epigenome-wide association studies (EWAS) using commercially available microarrays such as the Infinium HumanMethylation450 BeadChip assay ("450K," produced by Illumina, Inc.), its predecessor, the Infinium HumanMethylation27 BeadChip ("27K"), or an This article is part of the Topical Collection on Environmental Epigenetics older Illumina product based on the company's GoldenGate product.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide methylation profiles in maternal leukocyte DNA at the time of delivery show more methylation in women with pre-eclampsia compared to matched controls with an uncomplicated pregnancy. 41 Future research should examine whether differences in methylation contribute to the differential expressions of markers that are associated with pre-eclampsia. New biomarkers and pathways in pre-eclampsia could also be identified by differences in methylation.…”
Section: Genetic Studiesmentioning
confidence: 99%
“…9 We also demonstrated that, compared to normotensive controls, preeclamptic pregnancies are associated with an incomplete shift in normal hypomethylation resulting in a relative hypermethylation of much of the genome when measured at the time of delivery. 10 Pathway analysis of these differentially-methylated genes independently implicated the preeclampsia/eclampsia disease process with a P <9.97 × 10 −20 . 10 …”
Section: Discussionmentioning
confidence: 99%
“…9 We have also shown that maternal leukocyte DNA in preeclampsia cases at the time of delivery has an altered genome-wide methylation profile and that performing pathway analysis on these differentially-methylated genes independently identifies the PE disease state with high statistical significance. 10 In the current study, we sought to characterize the methylation patterns of 33 candidate genes in maternal leukocyte DNA in normal and preeclamptic pregnancies at delivery.…”
Section: Introductionmentioning
confidence: 99%